A Novel Classification for Diabetic Foot Ulcers of the First Ray. (January 2023) - Tamir, Eran; Rabau, Oded; Beer, Yiftah; Smorgick, Yossi; Kaufman, Hanna; Finestone, Aharon S.
ABSTRACT: OBJECTIVE: Diabetic foot ulcers of the first ray result from several distinct biomechanical mechanisms related to anatomical deformities, which must be addressed if surgical offloading is contemplated. The objective of this study was to create a classification of the anatomical deformities of first-ray ulcers that could lead to better standardization of treatment and reporting. METHODS: The authors performed a file review of patients with diabetic neuropathy diagnosed with first-ray ulcers over a period of 3 years in an outpatient setting. Anatomical deformities were diagnosed clinically and reported with ulcer location. The primary classification was the metatarsophalangeal joint, the interphalangeal joint, and the distal phalanx. RESULTS: Records for 59 patients (mean age, 62 years) with University of Texas A1 and A2 ulcers were reviewed. Mean ulcer duration was 2 months. The more common deformities were hallux valgus (41%), hallux valgus interphalangeus (14%), and hallux malleus (20%), and these were primarily associated with metatarsophalangeal, interphalangeal joint, and tip-of-toe ulcers, respectively ( P < .0001). CONCLUSIONS: By classifying ulcer locations, the relevant corrective surgery may be chosen. Although some prophylactic procedures may be safe and effective, prophylactic hallux valgus correction in the diabetic foot requires further study.